The Social Life of Musical Instruments by Eliot Bates (Orfeu, 2017)
This paper presents a review on thearticle The Social Life of Musical Instruments by Eliot Bates (2012). Bates makesa reflection about organology, criticizesthe old classificatory systems, commentson important works about organology andproposes a new paradigm based on theActor-Network Theory
Keywords: Organology; Musical instruments; Actor-Network Theory; Eliot Bates